Molecular detection and genotyping of intestinal protozoa from different biogeographical regions of Colombia (2020)
Background: Intestinal parasitic protozoa represent a serious problem of public health particularly in developing countries. Protozoa such as Blastocystis, Giardia intestinalis, Entamoeba histolytica and Cryptosporidium spp. are associated with diarrheal symptoms. In Colombia, there is little region-specific data on the frequency and circulating genotypes/species of these microorganisms. Therefore, the main objective of our study was to employ molecular detection and genotyping of G. intestinalis and Blastocystis, Cryptosporidium and Entamoeba spp. in samples from different biogeographical regions of Colombia. Methods: We collected 649 human fecal samples from five biogeographical regions of Colombia: the Amazon, Andean, Caribbean, Orinoco and Pacific regions. Blastocystis, G. intestinalis, Cryptosporidium spp. and Entamoeba complex were detected by microscopy and conventional PCR. Molecular genotyping was conducted to identify Blastocystis subtypes (STs) (18s), G. intestinalis assemblages (triose phosphate isomerase and glutamate dehydrogenase) and Cryptosporidium species (18s). Genetic diversity indices were determined using dnasp.5. Results: We detected G. intestinalis in 45.4% (n = 280) of samples, Blastocystis in 54.5% (n = 336) of samples, Cryptosporidium spp. in 7.3% (n = 45) of samples, Entamoeba dispar in 1.5% (n = 9) of samples, and Entamoeba moshkovskii in 0.32% (n = 2) of samples. Blastocystis STs 1-4, 8 and 9 and G. intestinalis assemblages AII, BIII, BIV, D and G were identified. The following Cryptosporidium species were identified: C. hominis, C. parvum, C. bovis, C. andersoni, C. muris, C. ubiquitum and C. felis. The Caribbean region had the highest frequency for each of the microorganisms evaluated (91.9% for G. duodenalis, 97.3% for Blastocystis, 10.8% for Cryptosporidium spp., 13.5% for E. dispar and 2.7% for E. moshkovskii). The Orinoco region had a high frequency of Blastocystis (97.2%) and the Andean region had a high frequency of G. intestinalis (69.4%). High and active transmission was apparent in several regions of the country, implying that mechanisms for prevention and control of intestinal parasitosis in different parts of the country must be improved. Copyright © 2020 Higuera et al.